2010
DOI: 10.1016/j.juro.2009.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Urethral Stricture After Pelvic Fracture Urethral Distraction Defects in Developing and Developed Countries, and Choice of Surgical Technique

Abstract: Differences in emergency treatment for pelvic fracture urethral distraction defects influence the choice of delayed posterior repair and results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…The mean age of the patients in current study corresponds with the study of Kulkarni S.B. et al (2010) [16] as they reported a median age of 33 years. Journal of Biosciences and Medicines…”
Section: Discussionsupporting
confidence: 87%
“…The mean age of the patients in current study corresponds with the study of Kulkarni S.B. et al (2010) [16] as they reported a median age of 33 years. Journal of Biosciences and Medicines…”
Section: Discussionsupporting
confidence: 87%
“…that lichen sclerosus was responsible for long, complex, multi‐focal strictures in the penile urethra, often requiring multiple interventions. External and iatrogenic trauma was the most important cause of posterior urethral pathology, although this population was much smaller in the present study than that seen in developing countries , or in countries where aggressive treatment for prostate cancer is practised . Nevertheless, this subgroup generated a large number of re‐operations because of the associated complexity.…”
Section: Discussionmentioning
confidence: 67%
“…success rates for all management techniques were 78% and 87%, for india and italy, respectively. 30 Stricture after prostate cancer therapy stricture disease after treatment for prostate cancer can occur anywhere from the bladder neck to urethral meatus. a publication reporting the incidence of stricture disease in patients from the CaPsure (Cancer of the Prostate strategic urologic research endeavor) database revealed an overall stricture treatment rate of 5% among men with a history of treatment for prostate cancer.…”
Section: Recurrent Pfuddsmentioning
confidence: 99%